Head injury because of free fall in neonates - Munayco Cortez, Carol (2021)
Objective: To describe clinical characteristics of head trauma in neonates. Material and methods: This is a case series of neonate patients with head trauma. All of them had a clinical diagnosis and computed tomography scans performed. They were taken care of in both Neuropediatrics and Neonatology services in Cayetano Heredia National Hospital in Lima, Peru from 2014 to 2019. Results: Twelve neonates were included, 67% (8/12) were male, 33% (4/12) were less than four days old, and 25% (3/12) were born to mature mothers. Free fall was the mechanism of lesion for all cases, and three of them fell down from baby trolleys. Places where these accidents occurred were at the hospital. Three neonates were in joint housing, two were in the waiting room of the outpatient clinic, and one fall occurred in the hospitalization ward. Eightythree per cent (10/12) of all cases fell from ≥0.5- m height, and 33% (4/12) fell from 1- m height. Fifty-eight per cent (7/12) developed symptoms after the fall, four had lethargy and one had irritability. Also, vomits and respiratory distress were reported. Four neonates developed epidural hematoma and three had cranial fracture, two of these latter cases were severe because of decompensated cranial hypertension that required emergency surgical decompression. Conclusion: Head trauma in neonates is a potentially severe condition. Epidural hematoma was the most frequent intracranial lesion. Lethargy and irritability were most frequent symptoms in neonates who fell from ≥0.5- m height.